Design and Simulation of methanol sensing devices using DMFC technology. Issue 1774 (2015) - Chittur K, Subramaniam; S, Muthuraja
ABSTRACT: Direct Methanol Fuel Cell, DMFC, technology, can be used for fabrication of sensors for volatile organic compounds like alcohols. A fundamental limitation in DMFC is methanol crossover. In this process methanol diffuses from the anode through the electrolyte to the cathode, where it reacts directly with the oxygen and produces no electrical current from the cell. This also results in poisoning of the cathode catalysts. The designed and fabrication of the sensor is by means of micro electro mechanical systems (MEMS) fabrication technology with electrochemical inputs. To achieve this we have used a passive mode design protocol using COMSOL Multiphysics. The design and simulation would involve optimization of various parameters, in the construction of the cell. We can optimize the overall power density and hence the sensitivity of the sensor by the modification of various parameters like the area of the working electrodes, separation distance and the electrode-electrolyte interface. A passive mode design protocol, for a cm cell area, using various parametric functions, and interfacing Darcy's law of fluidic flow through a porous medium, under specific pressure and temperature, was applied. The designing involves the construction of gas diffusion layers using carbon cloth for anode and cathode with various parametric variations. Nafion membrane was selected as proton exchange membrane for the construction with different interface structure to analyze the sensor's performance. Platinum and various alloy catalysts like Pt-Ru, Pt-Fe, Pt-Sn and Pt-Mo was chosen as the working catalysts. The parametric functions of the cell were optimized for ampherometric detection. It is proposed to design a MEMS based sensor with microfludic interconnects and its response characteristics will be studied.